Analytical Model for Seismic Performance of Hollow RC Bridge Piers Considering Elongation Reduction in Reinforcement Deteriorated by Aging and Other Factors - Tae-Hoon Kim; Ick-Hyun Kim; Hyun Mock Shin (International Journal of Concrete Structures and Materials)
Abstract This study presents an analytical technique for understanding the seismic behavior and evaluating the seismic performance of hollow RC bridge piers deteriorated by aging and other factors. Deterioration caused by de-icing agents and carbonation has reduced the lifespan of bridge structures, thus necessitating frequent maintenance and increasing economic and social costs. A validated nonlinear finite element analysis program RCAHEST (Reinforced Concrete Analysis in Higher Evaluation System Technology) was enhanced with a deterioration model and an extended damage index that incorporates elongation reduction in reinforcing bars. The modified nonlinear material model accounts for the reduction of cross-sectional area of reinforcement and the change of bond strength at the concrete-to-steel interface caused by corrosion. Extended damage indices considering elongation reduction of reinforcing bars aim to provide a means of quantifying numerically the damage in deteriorated hollow RC bridge piers under earthquake loading. This approach allowed for a reliable parametric study of deteriorated hollow RC bridge piers, resulting in accurate predictions of performance degradation and the reversal phenomenon of the damage index due to drift ratios. The proposed nonlinear analysis method was validated to properly account for key design variables, including corrosion level, yield strength and ultimate strength of the reinforcing bars, and compressive strength of the concrete. Additionally, the newly extended damage index, which incorporates both the deterioration model and elongation reduction in reinforcing bars affecting behavior, effectively evaluates seismic performance.